The carbon footprint of clinical trials: a global survey on the status quo and current regulatory guidance - Jean-Marc Hoffmann; Annina Bauer; Regina Grossmann (BMJ Global Health)
Introduction All economic sectors including the service sector, along with healthcare, education and research, need to reduce their greenhouse gas emissions to limit global temperature increases. In this study, we aim to globally assess the awareness and current actions taken by Academic Research Institutions (ARIs) or governments regarding the reduction of carbon dioxide equivalent (CO2e) emissions for clinical research.Methods We designed a cross-sectional survey-based study, which was distributed within the International Clinical Trials Center Network (ICN). The survey population comprised representatives of the ICN who had extensive experience in academic clinical research and profound knowledge and understanding of the local context.Results The response rate was 80%. Responding ARIs were from 15 different countries and 4 continents. Around half of the ARIs reported that almost none of their research projects considered reducing their carbon footprint. The other half of the ARIs were not familiar with this subject at all. According to 60% of the respondents, greenhouse gas emissions are not assessed by Institutional Review Boards (IRBs)/Ethics Committees (ECs) or competent authorities, while 40% did not know. Neither IRBs/ECs nor competent authorities currently advise sponsors and investigators on reducing the carbon footprint of their clinical research projects. As for reducing greenhouse gas emissions in clinical research, virtual conferences and meetings were the most commonly implemented measures by ARIs across all regions. Finally, we have put together an action plan/checklist advising researchers on carbon footprint reduction for clinical trials.Conclusion Currently, greenhouse gas emissions are neglected during the planning phase of a research project, and they are not yet addressed or assessed by default during the approval procedures by IRBs/ECs or competent authorities. Thus, all involved stakeholders within clinical research need to be made aware of it through advice from ARIs and IRBs/ECs, among others.